DAMPAK MEDIA SOSIAL TIKTOK TERHADAP PERILAKU SISWA KELAS V SEKOLAH DASAR NEGERI X - Ikhsanudin, Dani Mukhlis; Sri Hartatik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Use of TikTok Social Media Can Cause Both Positive and Negative Impacts. Excessive involvement in TikTok can lead to the emergence of trends. In this research, based on the identified problems, a study is needed on the impact of TikTok social media on the behavior of fifth-grade students at a public elementary school (SDN X). This study uses a qualitative method, with data collection techniques including observation, interviews, and student questionnaires. The purpose of this research is to understand the impact of TikTok on the behavior of fifth-grade students. The results of this study indicate that the negative impacts are more dominant. Students tend to follow trends found on TikTok. The negative impacts include a decline in students’ etiquette toward teachers, a decrease in manners and politeness, exposure to inappropriate content for children, students enjoying TikTok dance trends, reduced concentration during learning, and increased consumerist behavior due to exposure to product advertisements on TikTok. On the other hand, positive impacts include the use of TikTok as part of school assignments, TikTok being used as an ice-breaking activity during lessons, increased student confidence in expressing themselves, improved communication skills through vlogging content, opportunities for talented students in dancing and singing to practice, and using TikTok to seek knowledge. However, students in this study are still vulnerable to imitating content on TikTok and show a lack of awareness regarding the boundaries of social media usage, leading to excessive involvement.